An Analysis of National Education System Policy and Social Values - Abdul Latif Hutagaol; Makmur Syukri; Amiruddin Siahaan; Sri Rezeqi Rafiqah Wardah (Universitas Pahlawan Tuanku Tambusai, 2022)
Education policy is a joint regulation in the process of providing education. It is intended to be a reference for human resource management in education. This study aims to analyze educational policies and social values. This research approach is a qualitative type with a literature study method. Sources of research data are obtained from educational policy regulations, books, scientific articles, proceedings, and final assignments (thesis, thesis, or dissertation) that are relevant to the research theme. To check the validity of the research data, the triangulation technique was used. The results of this study indicate that educational policies and social values regulate the management of human resources at the national level and as management principles in educational institutions. The purpose of the policy is as a reference in structuring social values and protecting human rights, as well as being a guarantee for the fulfillment of citizens' rights to obtain education. In fact, this policy has become the government's “proof and promise” in favor of equal education for all people.